Pembelajaran Multipel Representasi Disertai Praktikum Pada Materi Ikatan Kimia - Gustafo Johansen Wilar; Sanusi Gugule (Chemistry Department, Universitas Negeri Manado, 2021)
The purpose of this study was to determine the effectiveness of Multiple Representations learning for chemical bonding material. This research was conducted at MA Muhammadiyah Talawaan Bajo in the academic year of 2020/2021. The research method used is descriptive qualitative. Twelve students of class X MIA were selected to be assigned as research samples. The data was collected by means of a test in the form of multiple choice questions as many as 15 items on chemical bonding materials. The data collection technique used the pretest and posttest questions. The test results obtained showed that there was a significant difference in student learning outcomes using multiple representations where the average score of students was 85.75 with N – Gain of 0.72 that classification as high. Based on these results it can be stated that as a result of learning using multiple representations of chemical bonding material, there is a development in students' knowledge.